Multilevel Marketing in Sharia Accounting Perspective - Budiandru, Budiandru; 'Ulhaq, Dhiya; Arianurzahra, Arianurzahra (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to determine how the implementation of accounting (transaction) sharia for PayTren products, and how to measure ushul fiqh against PayTren product.The method used in this research is descriptive research using documentation study approach,Data collection techniques used is the results of the research literature, social media, including on the Internet articles and television broadcasts. The implementation of Islamic sharia accounting, paytren has donerecordingcommissions, cashback, and also the recording of gifts arereasonable, because the recording is done based on the efforts being made.However, if seen based on the science of Usul Fiqh,the paytren in the first transactioncontains RIBA fadh'al, Then the second existence of inequity in the partners position, and there are elements of gharar (speculation) in the transaction activity.